Agri-food trade in Myanmar: Its role in Myanmar’s future economic takeoff - Diao, Xinshen; Masias, Ian; Lwin, Wuit Yi (International Food Policy Research Institute, 2020)
Agri-food exports are important for Myanmar’s economic takeoff, in particular for the transformation of agri-food systems. This paper analyzes the past performance of key agri-food exports and assess their role and future potential to contribute to the transformation of Myanmar’s agri-food system and the overall economy.